2014
DOI: 10.11113/jt.v66.2486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesh Number on Accuracy of Semi Submersible Motion Prediction

Abstract: Generally, floating structures play an important role for exploring the oil and gas from the sea. The force and motion prediction of offshore structures may be carried out by using time domain or frequency domain or model tests. In this paper the frequency domain analysis used because it is the simplified and linearized form of the equations of motion. Mostly in numerical calculations the number of meshes plays an important role in the accuracy of results, time of calculation and facing to computer memory limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The number of panels is 824 for each structure. [18] showed that by increasing mesh numbers almost two times, calculation time increases about five times and by increasing panel number in four times it reaches up to twenty times.…”
Section: Resultsmentioning
confidence: 99%
“…The number of panels is 824 for each structure. [18] showed that by increasing mesh numbers almost two times, calculation time increases about five times and by increasing panel number in four times it reaches up to twenty times.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing mesh number does not affect the accuracy of the calculated results except in the range of natural frequencies. Abyn et al (2014) [18] showed that by increasing mesh numbers almost two times, calculation time increases about five times and by increasing panel number in four times it reaches up to twenty times. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A model test related to interaction between semi-submersible and TLP was carried out by Hassan Abyn et al [12]. In continuing Hassan Abyn et al also tried to simulate the motion of a semi-submersible by using HydroSTAR and then analysed the effect of meshing number to the accuracy of execution result and execution time [13]. Besides, C. L. Siow et al also make a comparison on the motion of a semisubmersible when it alone to interaction condition by using previous experimental result [14].…”
Section: 20 Literature Reviewsmentioning
confidence: 99%
“…Where the M is structure mass, 𝐴 33 is heave added mass, 𝐵 33 is linear damping from diffraction potential theory, 𝑏 𝑣 is the viscous damping defined at Equation (13), c is the heave restoring force, and F is the wave force contributed to heave motion.…”
Section: Viscous Dampingmentioning
confidence: 99%
See 1 more Smart Citation